Formulation and Optimal Design of Dioscorea bulbifera and Honey-Loaded Gantrez®/Xyloglucan Hydrogel as Wound Healing Patches - Pattaranut Eakwaropas; Tanasait Ngawhirunpat; Theerasak Rojanarata; Prasopchai Patrojanasophon; Praneet Opanasopit; Nopparat Nuntharatanapong (MDPI AG, 2022)
Hydrogel patches are some of the most effective dressings for wound healing. In this study, the Gantrez® S-97 (Gan)/xyloglucan (XG) hydrogel patches were formulated by using a full central composite design (CCD). The optimized hydrogel patches consisted of 17.78% w/w of Gan and 0.1% w/w of XG. Honey and D. bulbifera extract were loaded in the Gan/XG hydrogel patches. The physical properties of the hydrogel patches, including water content, water absorption, rate of water vapor transmission, and mechanical properties, were examined. The D. bulbifera extract/honey-loaded patch exhibited a higher value of water absorption, tensile strength, and elongation than the honey-loaded patch and the unloaded patch, respectively. The biological activities of the patches were also investigated. All hydrogel patches protected wounds from external bacterial infection. The D. bulbifera extract/honey-loaded patch exhibited stronger antioxidant activity than the honey-loaded patch and the unloaded patch. Besides, all the hydrogel patches with concentrations of 0.5-2.5 mg/mL showed that they were nontoxic to fibroblast cells. The combination of D. bulbifera extract and honey in the patch affected fibroblast proliferation. In addition, all Gan/XG hydrogel patches significantly induced recovery of the scratch area. Therefore, the Gan/XG hydrogel patches could be candidates as wound dressings.